Astrocyte pathology in major depressive disorder: insights from human postmortem brain tissue - Rajkowska, Grazyna; Stockmeier, Craig A (Current drug targets, 2013)
The present paper reviews astrocyte pathology in major depressive disorder (MDD) and proposes that reductions in astrocytes and related markers are key features in the pathology of MDD. Astrocytes are the most numerous and versatile of all types of glial cells. They are crucial to the neuronal microenvironment by regulating glucose metabolism, neurotransmitter uptake (particularly for glutamate), synaptic development and maturation and the blood brain barrier. Pathology of astrocytes has been consistently noted in MDD as well as in rodent models of depressive-like behavior. This review summarizes evidence from human postmortem tissue showing alterations in the expression of protein and mRNA for astrocyte markers such as glial fibrillary acidic protein (GFAP), gap junction proteins (connexin 40 and 43), the water channel aquaporin-4 (AQP4), a calcium-binding protein S100B and glutamatergic markers including the excitatory amino acid transporters 1 and 2 (EAAT1, EAAT2) and glutamine synthetase. Moreover, preclinical studies are presented that demonstrate the involvement of GFAP and astrocytes in animal models of stress and depressive-like behavior and the influence of different classes of antidepressant medications on astrocytes. In light of the various astrocyte deficits noted in MDD, astrocytes may be novel targets for the action of antidepressant medications. Possible functional consequences of altered expression of astrocytic markers in MDD are also discussed. Finally, the unique pattern of cell pathology in MDD, characterized by prominent reductions in the density of astrocytes and in the expression of their markers without obvious neuronal loss, is contrasted with that found in other neuropsychiatric and neurodegenerative disorders.